G43(P) RCPCH QI diabetes collaborative: improving the clinic experience. (May 2019) - Abitha Kujambal, V; Brown, J; Rookes, R; Cheney, S; Balapatabendi, M; Matthai, S; Dembenski, K; Odeny, I
Abstract : Introduction: Gloucestershire Paediatric Diabetes Team has implemented several innovations including carbohydrate counting from diagnosis, annual review clinics and family events. We seek to improve our patient engagement and experience to improve health outcomes. Aim: Improve the clinic experience for patients, their families and staff, based on their input, thereby encouraging greater engagement and patient attendance as part of the RCPCH quality Improvement programme Methods: We undertook mapping of our current clinic process and ideal clinic. We collected feedback from patients, families, clinic staff and our team members. We identified main areas for improvement. Interventions were implemented and evaluation done. Interventions and results: Conclusion: Verbal and written feedback has shown families and children are engaging to a greater extent (table 1 ) and more involved in their own diabetes management. They are more relaxed and have now found their voice. The project has enabled us to improve our team working.